Structure And Role Of Actors In Social Networks Moa Buffalo Farmer In Klis Village Maluku Regency Southwest Maluku Province - Melianus Ririmase, Pieter; Melkianus Puttileihalat, Paulus; Willem Patty, Christian (Journal of World Science, 2022)
Buffalo farmers in Klis Village in their development need to prioritize social values ??as the strength of the relationship between their members in interacting. Interaction shows the existence of a relatively stable relationship and shows the existence of a learning process that leads to strengthening the capacity of individuals or groups. The level of interaction can be described through the structure of the relationship between farmers (actors) in the social network and the role of each actor, to receive and share information so that it can show the pattern of relationships and the importance of actors in a network. This study aims to examine the structure of social networks and the role of actors in the social network of moa buffalo farmers in Klis Village, Moa District, Southwest Maluku Regency. The results showed that the social network structure of farmers at each click was in the form of an Interlocking Personal Network. Networks that have interlocking properties are networks that have a high degree of integration within the group but have low openness outside the group. Actors 11, 8, 27 and 23 are actors who have an important role in the social network of buffalo farmers, namely as; opinion leaders, gate keepers, bridges, and liaisons.